Causação cumulativa, taxa de câmbio real e progresso tecnológico endógeno em uma abordagem dinâmica de mudança estrutural multilateral: uma análise teórica e empírica - Paiva, Matheus Silva de (2015)
The work aims to develop a multi-sectoral cumulative causation model with endogenous technological progress. The export-led growth literature, originally based in Dixon and Thirlwall (1979) model, advanced to a multi-sectoral approach by Araujo (2013). However, the multisectoral model originally developed by Araujo and Lima (2007), disregards the exchange rate and keeps the rate of change of labor productivity null. Thus, we intend to advance the theoretical debate by introducing the Pasinettiano model endogenous technological progress and the real exchange rate in the Law of Multi-Sectoral Thirlwall. This contribution becomes important to enable policy makers to identify which sectors contribute most to the long-term growth of the domestic economy as well as providing economic and industrial policies to improve trade relations and the competitiveness of the economy, to drive the economy to a higher stage of development.